A Community-Based Home Visitation Program's Impact on Birth Outcomes. Issue 1 (January 2016) - Guo, Yuqing; Pimentel, Pamela; Lessard, Jared; Rousseau, Julie; Lee, Jung-Ah; Bojorquez, Yvette; Silva, Michele; Olshansky, Ellen
Abstract: Background: MOMS Orange County is a coordinated home visitation program in which trained paraprofessional home visitors work under the close supervision of registered nurses. This model was developed to address health disparities in birth outcomes in a Hispanic community in Orange County, CA. Purpose: The primary objective was to test the impact of MOMS Orange County on birth outcomes. The second objective was to examine the breadth of prenatal health education topics as a mediator of the relationship between home visits and birth outcomes. Methods: A retrospective cohort design was used. Paraprofessional home visitors collected prenatal and postnatal data during home visits. Only those whose birth outcomes were obtained were included in the analysis ( N = 2, 027 participants). Regression models were conducted to test the associations between prenatal home visits and birth outcomes, adjusting for 10 covariates. Results: Number of prenatal home visits predicted higher birthweight and greater gestational age at birth. Breadth of health education topics partially mediated the associations between home visits and birthweight. The same mediation was revealed with gestational age at birth. Clinical Implications: The MOMS Orange County prenatal home visitation program may be a promising approach to decrease adverse birth outcomes in disadvantaged communities. Rigorously designed studies are needed to further test this model. Abstract : Home visiting programs are a promising approach to decrease adverse births outcomes in disadvantaged communities.